2018
DOI: 10.1126/science.aau1311
|View full text |Cite
|
Sign up to set email alerts
|

Animals feel safer from humans in the dark

Abstract: Mammals shift their activities to twilight and night hours in response to human disturbance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…At disturbed latrines, the frequency of daytime visits and defecation events was depressed even further. This is similar to observations in other carnivore species that have adapted to a synanthropic lifestyle (e.g., red foxes, coyotes, raccoons, European badgers; Sálek et al ), often by changing their activity patterns to become predominantly, or even exclusively, nocturnal (McIntyre , Benítez‐López , Gaynor et al ). Other studies (Zhou et al ) reported that a wide variety of other carnivore species (e.g., yellow‐throated martens [ Martes flavigula ], masked palm civets) were deterred from defecating close to areas of heightened human activity, and thus changed their temporal and spatial latrine‐use pattern.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At disturbed latrines, the frequency of daytime visits and defecation events was depressed even further. This is similar to observations in other carnivore species that have adapted to a synanthropic lifestyle (e.g., red foxes, coyotes, raccoons, European badgers; Sálek et al ), often by changing their activity patterns to become predominantly, or even exclusively, nocturnal (McIntyre , Benítez‐López , Gaynor et al ). Other studies (Zhou et al ) reported that a wide variety of other carnivore species (e.g., yellow‐throated martens [ Martes flavigula ], masked palm civets) were deterred from defecating close to areas of heightened human activity, and thus changed their temporal and spatial latrine‐use pattern.…”
Section: Discussionsupporting
confidence: 87%
“…We hypothesized that if raccoon dogs perceive human activity as a predation risk (Clinchy et al ), they may alter or modify their behavior in accord with the risk‐disturbance hypothesis (Frid and Dill ), shifting activity patterns towards nocturnal latrine use (Benítez‐López , Gaynor et al ). Thus, we predicted that level of human disturbance would affect timing of latrine visits and defecation events, but that overall latrine‐use frequency would not be affected by disturbance, and that raccoon dogs would continue to use disturbed latrines because olfactory information exchanged at latrines is crucial in this species to maintain stable socio‐spatial networks.…”
mentioning
confidence: 99%
“…Top‐down, bottom‐up and physical environment effects of human activities may also alter ecosystem dynamics through shifts in the timing and distribution of animal activities, such as increasing nocturnality (Benítez‐López 2018; Gaynor et al . 2018) and avoidance of or attraction to developed areas (Leblond et al .…”
Section: Linking Human‐induced Behaviour Change To Ecological Functionsmentioning
confidence: 99%
“…As diurnal “super predators”, humans dominate 75% of Earth’s land surface and are driving increases in nocturnal activity in medium- and large-bodied mammals (Benítez-López, 2018). A recent meta-analysis of 76 studies of 62 mammalian species on six continents (Gaynor et al., 2018) revealed a strong effect of human presence on the temporal activity of wildlife, with an average 36% increase in nocturnal activity in response to human disturbance.…”
Section: Discussionmentioning
confidence: 99%